Comparative analysis of methods for the treatment of acute epididymitis in children - A. Yu. Pavlov; D. N. Shchedrov; P. N. Polyakov (Бюллетень сибирской медицины)
The results of treatment of acute epididymitis is analyzed. The materials were 101 patients aged 17 years, catamnesis followed in terms of 1 to 10 years. We used a conservative, surgical and puncture treatment method proposed by the authors. Analyzed clinical, ultrasound and Doppler sonography parameters. It is shown that best results are obtained with conservative treatment, the results of treatment are comparable to puncture them for efficiency, with surgical intervention results are less satisfactory.